Visualizing Staff Information System (VSIS) / Wong Mook Lan - Wong , Mook Lan (2001)
The Visualizing Staff Information System also known as VSIS is a system to keep track the personal record of the staff in a company and with effective visual displays which concerned with exploring data and information to gain insight and understanding of the data. The software development tool used are Visual Basic 6.0, Seagate Crystal Report 7.0 and Microsoft SQL Server 7.0 is used as a database management system. Prototype model is conducted in the system development. Before an interview was conducted, a set of interview questions were prepared and sent to the respective company. Global Soft Manufacturing was one of the correspondent companies. An interview session was carried out with the senior manager who is in charge of the staff personal record and working schedule. The interview has helped in gathering raw data for this system. The features that are included in the system are user friendliness, flexibility, reliability and security measures. The main objective of this system is to fulfil the needs of the manager or the administrator in order to reduce paper work and process time.